Labor market rigidities and unemployment in Europe - Horst Siebert (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
The paper studies the major institutional changes that are at the root of the increase in the west European unemployment rate in the last quartercentury from below 3 percent to 11 percent. The institutional characteristics of wage bargaining, the tax wedge and the legal rules hamper the self-equilibrating function of the labor market. The reservation wage, implicitly increased by the rise of the welfare state, has affected the bargaining process, the wage level and the wage structure. Econometric evidence is presented. Unemployment differs depending on the Scandinavian, the French-Mediterranean, the German and the British-Dutch approach to the labor market.
Keywords: J20; J30; J50; 330; Arbeitslosigkeit; Arbeitsmarkt; Institutionalismus; Lohnpolitik; Sozialstaat; Arbeitsrecht; Europa